HABERMAS ON RELIGION, LAW STATE, AND PUBLIC SPHERE - KURNIAWAN, WIWIT (Jurnal Ilmiah Humanika, 2020)
Articulating religious interest in secular public sphere is always elusive. Because it bring vast consequences for political and social aspect in a law state realism. A democratic state that stakes law supremacy has an obligation to accommodate every interest of their citizen and offer freedom of speech. Nevertheless, the emergence of religious articulation conveying doctrines and divisive argument tents to the dead-lock discussion among citizen. Certain law that in favors to particular religious interest also bloom discontent of other religions. Herbermas delivered a notion about communicative action that is able to implement to tackle this maze problem. This paper scrutinize Habermas theory and its relevant on the discourse of religion in the public sphere.